A Study of Culinary Business Marketing Strategies Using Influencers Amidst Weakening Consumer Purchasing Power - Luckhy Natalia Anastasye Lotte; Silvia Ekasari; Dadang Suhardi; Susanto; Halim Dwi Putra (Indonesian Journal of Business Analytics, 2026)
The culinary business economy operates within a highly complex environment where operational efficiency meets constantly evolving consumer psychology. A closer look reveals that the sector's economic foundation lies in managing production costs, which are highly sensitive to changes in fiscal policy and volatility in upstream food commodity prices.  The purpose of this study is to provide a study of culinary business marketing strategies using influencers amidst weakening consumer purchasing power. This research uses a qualitative approach in the form of a strategic study. This study is supported by secondary data such as books, journals, and related sources. The results of this study indicate that marketing strategies using influencers amidst weakening consumer purchasing power require a paradigm shift from simply creating desire to justifying spending on culinary businesses. Today's consumers are more selective and tend to seek real value rather than mere visual trends. The study of culinary marketing strategies using influencers in challenging economic conditions includes a shift in selection, content emphasis, strong call-to-action promotional strategies, utilization of short video platforms, and rigorous measurement of return on investment.